2021
DOI: 10.1002/bse.2898
|View full text |Cite
|
Sign up to set email alerts
|

Connection to nature and sustainability in small‐ and medium‐sized environmental organizations: A dynamic strategic thinking approach

Abstract: Strategic thinking has evolved from a concept predominantly based on analysis, closely integrated with strategic planning, to a broader mindset, yet it remains strongly 'head based'. The aim of this paper is to explore a context where a broader, more holistic perspective exists, focused on the connection of small-and mediumsized environmental organizations with the natural world, why and how this relationship influences strategic thinking and how it enables organizations to leverage limited resources. The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Consequently, we consider even this small presence of intrinsic value (and deep ecology) within narratives (and 24 disclosures) to be noteworthy, acknowledging that two other studies identified companies “embedding deep ecological culture” (Hassan et al, 2021; Roberts, Nandy, et al, 2021, p. 19). Indeed, the presence of these values may be indicative of a firm with ecocentric leadership underpinning business strategy (Biswas et al, 2022; Karami & Gorzynski, 2022). Corporate reporting has included narratives conveying habitat restoration/protection, although this has been associated with reputation management (and legitimising operations) (Atkins et al, 2018; Gray & Milne, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, we consider even this small presence of intrinsic value (and deep ecology) within narratives (and 24 disclosures) to be noteworthy, acknowledging that two other studies identified companies “embedding deep ecological culture” (Hassan et al, 2021; Roberts, Nandy, et al, 2021, p. 19). Indeed, the presence of these values may be indicative of a firm with ecocentric leadership underpinning business strategy (Biswas et al, 2022; Karami & Gorzynski, 2022). Corporate reporting has included narratives conveying habitat restoration/protection, although this has been associated with reputation management (and legitimising operations) (Atkins et al, 2018; Gray & Milne, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of deep ecology values (i.e., in over half of disclosures) is notable and, again, may evidence a response to growing deep ecology pressures (Hassan et al, 2021; Roberts, Nandy, et al, 2021) as well as ecocentric leadership informing business strategy (Biswas et al, 2022; Karami & Gorzynski, 2022). This indicates corporations could support the sustainable protection of all biodiversity (Batavia & Nelson, 2017; Bond et al, 2021; Taylor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies considering which stakeholders are involved in the innovation process and identifying the needs and the synergistic sustainability effects that the innovation is intended to produce. In this regard, the research has been paying attention to the dynamics of design thinking (Goodman et al, 2017), addressing ways to overcome the constraints of its application and investigating how it can be integrated into sustainable management models (Karami & Gorzynski, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%